Renal and intrarenal blood flow in non-cirrhotic portal hypertension. Issue 10 (October 1972) - Kew, M. C.; Limbrick, Carol; Varma, R. R.; Sherlock, Sheila
Abstract : The effect of portal hypertension or the consequent portal circulatory changes on renal haemodynamics was studied using the 133 xenon washout technique. Renal blood flow was reduced in nine of 11 patients with non-cirrhotic portal hypertension and this was accompanied by a redistribution of intrarenal blood flow, the distribution to and flow rate through the outer cortex being reduced while juxtamedullary and medullary flow was maintained. With slight or moderate decreases in cortical flow glomerular filtration was normal but poor cortical perfusion was associated with low creatinine clearances. These findings raise the possibility that portal hypertension or portal circulatory changes may play a role in the pathogenesis of the renal haemodynamic changes and functional renal failure which frequently complicate advanced hepatic cirrhosis.